Pengabdian Kepada Masyarakat Nagari Pilubang Melalui Kegiatan Pendampingan Pendidikan - Yanti, Silvia Rahma; Amelia, Ulfi; Mugits, Muhamad Mikdam (LPPM STAI Darul Falah, 2025)
Education plays a crucial role in human development and improving the quality of life within communities. In Nagari Pilubang, Padang Pariaman Regency, the level of education remains low, which impacts the employment choices of most of the population, who rely on the agricultural and fisheries sectors. This research aims to improve community education through an educational assistance program focusing on religious study guidance and socialization activities. This study employs a descriptive qualitative approach with thematic data analysis techniques. Data were collected through interviews, observations, and documentation at the research site. Data was analyzed by reducing data, presenting it as descriptive narratives, and drawing conclusions based on the identified themes. The study and socialization activities, such as the Clean and Healthy Lifestyle behavior guidance conducted at several schools in Nagari Pilubang, showed positive impacts for students who received additional learning and for the community, which became more aware of the importance of education and health. This program encouraged students to study more diligently, boosted their motivation, and fostered healthy living habits that benefit daily life. It is expected that, through this program, the Pilubang community will be able to develop their potential, improve their standard of living, and create sustainable change. This research also provides a deeper understanding of the community's support in enhancing education and welfare in Nagari Pilubang.